2007
DOI: 10.1111/j.0030-1299.2007.15935.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian species richness across environmental gradients

Abstract: Large-scale field patterns are a fundamental source of inferences on processes responsible for variation in species richness among habitats. We examined species richness of larval amphibian communities in 37 ponds over seven years on the Univ. of Michigan's E. S. George Reserve. Ordination of the community incidence matrix indicated a strong major axis of variation in species associations that was correlated with pond hydroperiod, surface area and forest canopy cover. Communities were significantly nested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
198
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(212 citation statements)
references
References 57 publications
(89 reference statements)
7
198
0
7
Order By: Relevance
“…Canopy coverage has been increasingly implicated in the performance, abundance, distribution, and diversity of a variety of aquatic species ( Nilsson & Svensson, 1995;Skelly et al , 1999;Grether et al , 2001;Hill et al , 2001;Halverson et al , 2003;Batzer et al , 2004;McCauley, 2005;Schiesari, 2006;Werner et al , 2007;Williams et al , 2007 ). Changes in forest cover associated with changing forestry and agricultural practices, habitat restoration efforts, and alterations of natural disturbance regimes ( Frost, 1995 ;Tilman et al , 2000;Caspersen et al , 2000;Schurbon & Fauth, 2003;Chen et al , 2006 ) may have unforeseen consequences for associated aquatic systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Canopy coverage has been increasingly implicated in the performance, abundance, distribution, and diversity of a variety of aquatic species ( Nilsson & Svensson, 1995;Skelly et al , 1999;Grether et al , 2001;Hill et al , 2001;Halverson et al , 2003;Batzer et al , 2004;McCauley, 2005;Schiesari, 2006;Werner et al , 2007;Williams et al , 2007 ). Changes in forest cover associated with changing forestry and agricultural practices, habitat restoration efforts, and alterations of natural disturbance regimes ( Frost, 1995 ;Tilman et al , 2000;Caspersen et al , 2000;Schurbon & Fauth, 2003;Chen et al , 2006 ) may have unforeseen consequences for associated aquatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…If species behaviourally avoid low-quality habitats, expected changes in population or metapopulation size can be mediated, assuming a sufficient high-quality habitat remains accessible. Documented local extinction events in closed canopy ponds ( Skelly et al , 1999;Werner et al , 2007 ) could be behavioural phenomena, depending on the strength of the avoidance or attraction. Although more work is necessary in quantifying colonisation at intermediate canopy levels, we have demonstrated that the extremes of this gradient produce strong spatial variation in colonisation dynamics, as opposed to simply generating local variation in performance and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar de sua importância, a determinação da composição de espécies e da diversidade em uma área podem ser difíceis de serem identificadas corretamente, dada a variação de complexidade das relações ecológicas em que cada táxon está inserido (ricKlefs & schluTer, 1993;chesson, 2000;Werner et al, 2007;GoTelli et al, 2009). No caso dos anfíbios anuros, correlações positivas têm sido encontradas tanto entre riqueza e fatores bióticos, como por exemplo, a competição direta por recursos com espécies invasoras (Pearl et al, 2004) e a predação de girinos por espécies de peixes (PillioD et al, 2010) quanto por fatores abióticos, como por exemplo a fragmentação florestal (bell & Donnely, 2006) e a heterogeneidade ambiental (Keller et al, 2009).…”
unclassified